The Impact Of Artificial Intelligence On Accounting Information Systems - Sanjiwani, Putu Diah Aryastuti; Anak Agung Intan Wulandari; Gita Apsari Dewi; Muhammad Prans Panca Renta (Jurnal Ekonomi, 2024)
While AI technologies offer remarkable opportunities for improving efficiency and accuracy in accounting processes, it is essential to carefully consider and address the challenges and opposing arguments that arise with their implementation. This includes ensuring ethical use, addressing job displacement concerns, enhancing data security and privacy, and mitigating bias in AI algorithms to uphold the integrity of accounting practices. In this study, conducted a literature review to explore the impact of AI technologies on accounting information systems. The results show the integration of AI in fraud detection processes has proven to be instrumental in improving the interpretability of fraud detection methods, addressing emerging fraud patterns, and mitigating the challenges posed by imbalanced datasets. Additionally, the emphasis on education and training in AI technologies for accountants underscores the imperative of equipping professionals with the necessary skills to effectively implement AI-based solutions in fraud detection and prevention. Furthermore, there is a need to delve deeper into the ethical considerations surrounding AI in financial reporting, with a specific emphasis on mitigating biases, ensuring data privacy and security, and upholding transparency and accountability in the use of AI systems.